Ressignificações do seminário acadêmico em cursos de bacharelado na UFMT - Luz, Antônia Cristina Valentim da (2020)
This master's thesis showed the results of an investigation that sought to understand the theoretical and methodological concepts underlying the academic seminar practices in four bachelor's courses at the Federal University of Mato Grosso, on the Cuiabá campus. Such subjects were selected due to the need to develop the oral communication skills described in the official documents of these courses. The starting point of the investigations were questions about what would be the definition of an academic seminar for students of Bachelor's courses, how would the practice be guided by teachers, what would the teaching plans documents about gender and what would be the theoretical- methodology underlying the practice. We base our research on the ideals of contemporary Applied Linguistics that seeks to study linguistic practices from the point of view of the subjects, combined with the theoretical perspectives of gender study of socio-discursive interactionism and we adopt some concepts of socio-rhetoric. The methodology employed is a qualitative and quantitative approach that allows a broader and more intelligible idea of the complexity of a problem. We tried to investigate the conceptions in the teaching plans and in the subjects' definitions, comparing the data. Then we focused on the subjects' perceptions and ended by analyzing whether the concepts were reflected in the practices. The data revealed that the theoretical-methodological concepts underlying the practices of SA are from a didactic-pedagogical perspective that conceive it as a teaching technique or method, considering as communicative purposes: teaching, transmitting content and evaluating learning. Such conceptions are reflected in the studied practical production, in which we perceive the lack of guidelines that show the characteristics of the oral genre and the privilege of aspects aimed at apprehending the contents of the discipline.